2017
DOI: 10.1128/msphere.00352-16
|View full text |Cite|
|
Sign up to set email alerts
|

Human Norovirus Evolution in a Chronically Infected Host

Abstract: The norovirus genogroup II genotype 4 (GII.4) variants have approximately 5% divergence in capsid amino acid identity and have dominated over the past decade. The precise reason(s) for the GII.4 emergence and persistence in the human population is still unknown, but some studies have suggested that chronically infected patients might generate novel variants that can cause new epidemics. We examined GII.4 noroviruses isolated from an immunocompromised patient with a long-term infection. Numerous norovirus capsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…Consistently with the studies mentioned above, in a clinical retrospective study a correlation between high levels of α2′‐linked fucosylated HMOs in breast milk and protection against Calicivirus ‐associated diarrhea has been reported . Further investigations should also consider 3‐fucosyllactose and 3‐fucosylated HMOs, as they also bound at the HBGA binding site in the X‐ray crystallography and MS/MS studies …”
Section: Role Of Glycans In the Viral Attachmentsupporting
confidence: 75%
“…Consistently with the studies mentioned above, in a clinical retrospective study a correlation between high levels of α2′‐linked fucosylated HMOs in breast milk and protection against Calicivirus ‐associated diarrhea has been reported . Further investigations should also consider 3‐fucosyllactose and 3‐fucosylated HMOs, as they also bound at the HBGA binding site in the X‐ray crystallography and MS/MS studies …”
Section: Role Of Glycans In the Viral Attachmentsupporting
confidence: 75%
“…3) might exert additional influence on the efficiency with which Saga-2006 and NSW-2012 VLPs bind to HBGAs present in PGM. Indeed, a similar kind of varied level of HBGA binding and inhibition was also observed with genetically related GII.4 noroviruses isolated from a chronically infected individual (33).…”
Section: Resultssupporting
confidence: 55%
“…To begin to evaluate HuNoV infection, we showed that HuNoV RNAs are present within Vero cells following a 1 h or 6 h incubation by qRT-PCR ( Figure 1A). HuNoVs use HBGAs, such as the H-antigen, as attachment factors [55][56][57]; however, they are not a requirement for HuNoV infection [58][59][60][61][62]. We examined the level of H-antigen expression on Vero cells or Caco-2 cells and showed that Vero cells do not express the H-antigen by ELISA ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%